2011
DOI: 10.5539/mas.v5n3p173
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Performance of Gas Turbine Power Plant with Effect Intercooler

Abstract: A cycle model of a gas turbine power plant with effect intercooler along with a detailed parametric study is presented in this paper. The effects of parameter (design and operation condition) on the power output, compression work, specific fuel consumption and thermal efficiency are evaluated. In this study, the implementation of intercooling increases the power generating efficiency of the suggested gas turbine power plant when compared to the non-intercooled gas turbine power plant, configurations. Intercool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Al-Doori [ 18 ] investigated the effect of using an intercooler on the parametric performance of a gas turbine power plant. He simulated the effects of design and operational parameters on power output performance factors such as input compressor work done, the rate of fuel consumption, and thermal efficiency of the plant cycle, including the comparative performance of gas turbine plants with and without intercoolers.…”
Section: Gas Turbine Power Plant Equipment Performance and Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Al-Doori [ 18 ] investigated the effect of using an intercooler on the parametric performance of a gas turbine power plant. He simulated the effects of design and operational parameters on power output performance factors such as input compressor work done, the rate of fuel consumption, and thermal efficiency of the plant cycle, including the comparative performance of gas turbine plants with and without intercoolers.…”
Section: Gas Turbine Power Plant Equipment Performance and Improvementsmentioning
confidence: 99%
“…In Ref. [ 18 ], a recuperator heat exchanger was manufactured from a carbon/carbon matrix composite and used in a nuclear power plant. The aim was to simultaneously increase the efficiency of the gas Brayton cycle system, which incorporated a recuperator and substantially reduce the system’s mass as the recuperator accounted for nearly half the weight of the energy conversion system.…”
Section: Gas Turbine Power Plant Equipment Performance and Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors findings showed that the optimal specific heat ratio had increased as a result of the overall cycle pressure ratio decreasing, whereas a lower increase can be gained with higher intercooling pressure ratios. Al-Doori [25] studied the effect of different parameters, such as operation condition and design, on the power output, specific fuel consumption, compression work, and thermal efficiency of a gas turbine power plant with and without an intercooling system. The outcome of the research showed that the power generation efficiency of the power plant has improved by 9% from utilizing the intercooling system and that the performance of the intercooled gas turbine cycle can be further enhanced when both peak temperature and total pressure ratios are increased.…”
Section: Gas Turbines Intercooled System and Their Designsmentioning
confidence: 99%
“…With the help of GT PRO software the performances of a 100 MW gas turbine model were analyzed, for a various types of inlet air cooling systems, and it had been reached that a decrease of air temperature of 1 0 C (in the 25-35 0 C interval) leads to an increase in power output of approximately 0.7 MW [11]. For a gas turbine cycle, with intermediate cooling (intercooler), the decrease of inlet air temperature causes the output power to rise and the intercooling leads to a 5-9% gain of power and a 8% reduction in fuel consumption [12]. Reduction of fuel consumption represents a priority both for industrial gas turbine manufacturers and also for the civil aviation.…”
Section: Introductionmentioning
confidence: 99%